IMPLEMENTASI BERMAIN SEBAGAI METODE PEMBELAJARAN DALAM PENDIDIKAN ANAK USIA DINI - Ariani Nasution; Sri Ratna Dewi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Abstract Everyone definitely wants the presence of a child who can fill the household with happiness. The presence of a child in the family is highly anticipated by a mother. So the role of parents is very important in taking care of children from childhood to adulthood. They play a role in providing good education in terms of any science, including in terms of religious knowledge, providing sufficient love and attention to children's growth and development until they grow into independent individuals. Many of us know how to educate children in their golden years where they can grow up in a good environment and learning is not an enemy for them because during that period children can easily get bored in a monotonous way and they need entertainment that keeps them happy while learning. without getting bored. So the idea arose to make a game while studying and play it in the middle of the lesson or after studying was finished to make them fresh again to receive new lessons. Playing while learning has benefits and influences for children, including strengthening their physique through muscle movement, developing independence, improving communication. The types of games that can be played are through social play methods, playing with objects and role playing. Each of these methods has its own advantages and disadvantages, but the important thing is not to force learning that is less profitable on them, because basically the world of children is a world of play, playing while learning or learn through play methods.